Iraqi EFL university students’ word recognition strategies and vocabulary proficiency: A correlational study - Kadhim, Balqees Hameedi; Al-Bakri, Shaymaa Abul Baqi (Edelweiss Applied Science and Technology, 2024)
Word recognition is a cognitive activity widely acknowledged as a hallmark of fluent L2 readers. Understanding a text can only be accomplished with the ability to decode printed words efficiently. Another factor affecting students’ comprehension is vocabulary. Therefore, this research aims to investigate whether there is any significant relationship between word recognition strategies and vocabulary knowledge among Iraqi university students. This study made use of four instruments to collect the data. A comprehensive framework for evaluating students’ vocabulary proficiency consists of two tests: one measures the reception and production of vocabulary information and the other assesses orthographic coding and phonological decoding procedures. The results show that the respondents use both strategies to an average degree with over-reliance on the orthographic one in recognizing English words by employing a descriptive correlational research design with 400 respondents. Furthermore, a positive relationship was observed between word recognition strategies and vocabulary proficiency.